Human Characteristics In Religious Scripture: An Analytical Study On Sensory Hearing And Seeing - Abdoul Karim Toure; Robiatul Adawiyah Mohd @ Amat; Ahmad Kamel Mohamed; Abd Muhaimin Ahmad; Mesbahul Hoque; Adnan Mohamed Yusoff (IAEME Publication, 2024)
Human beings with power of senses (Ḥawās) for the purpose of feeling through seeing, touching, smelling, hearing and tasting with the aids of major organs of man, ranging from eye, hand, nose, ear and tongue or mouth. It is with this power of sense that human beings are raised in status and position above all other animals.. However, Qur’ān addresses its significance in relation to human beings and building of their characters. Sūratul-Baqarah is one of the chapters of the Qur’ān that discusses that. Out of these senses; hearings and sights or visual and audio are very significant that are worthy of study in this paper. It suggests that, apart from old age that can cause damage to the brain, wrong characters to include rebellion to instructions of Allah usually lead to its dysfunction. According to the SūratulBaqarah, the combination of the two sensitive organs of hearing and seeing helps greatly in grasp knowledge and characters building. Conclusively, Sūratul-Baqarah plays substantive role in building human characters. Characters like sincerity, uprightness, trust, righteousness etc. Key words: Character-building, Sūrah al-Baqarah, Senses, Hearing, Sight.